Ngā Māuiui Kai: creating Indigenous Māori terms for eating disorders in Aotearoa New Zealand - Gloria Fraser; Mau Te Rangimarie Clark; Bailey Mary Rose; Kacey Martin; Brittani Beavis; Michaela Pettie; Jennifer Jordan; Keri Opai (Journal of Eating Disorders)
Abstract Background Māori (the Indigenous people of Aotearoa New Zealand) report higher rates of eating disorders than non-Māori, but access treatment at lower rates. Diagnostic terms lacking in cultural relevance likely contribute to Māori exclusion in eating disorder spaces. Developing terms in te reo Māori (the Māori language) presents an opportunity to challenge eating disorder stereotypes and increase cultural safety in the eating disorder workforce. Methodology Guided by a Māori worldview and the practice of wānanga (to meet, discuss, and think deeply about a topic), we present a Māori language glossary for eating disorders. The glossary is informed by expertise in te reo Māori, mātauranga Māori (the body of Māori knowledge), and eating disorders, and combines terms already in use with newly developed terms. Results We propose an umbrella term for eating disorders (ngā māuiui kai), as well as terms for anorexia nervosa (māuiui whakatiki), bulimia nervosa (pukuruaki), binge eating disorder (māuiui kaihoro), and avoidant restrictive food intake disorder (karo kai, with three subtypes of low interest [arokore kai], sensory-based avoidance [āmaimai rongo kai], and concern about the consequences of eating [wehi-ā-kai]). We also propose terms for related concepts of body image difficulties (māuiui whakawā ata), perfectionism (māuiui kōtihitihi) and emotion dysregulation (kare-a-roto kōtitititi). Conclusion This glossary is available for use by anyone looking for terms that come from a mana-enhancing (empowering, respectful, and strengths-based) Māori worldview. The kupu (words, terms) in this glossary are offered as possibilities for use, rather than as definitive or correct, in the hopes they will promote discussion about stigma, indigeneity, and language in the eating disorders field.